Immunoglobulin (Ig)M antibodies to proteinase 3 in granulomatosis with polyangiitis and microscopic polyangiitis. (7th February 2017) - Clain, J. M.; Hummel, A. M.; Stone, J. H.; Fervenza, F. C.; Hoffman, G. S.; Kallenberg, C. G. M.; Langford, C. A.; McCune, W. J.; Merkel, P. A.; Monach, P. A.; Seo, P.; Spiera, R. F.; et al.
Summary: Anti‐neutrophil cytoplasmic antibodies (ANCA) appear to play an important role in the pathogenesis of ANCA‐associated vasculitis (AAV). However, ANCA alone are not sufficient to generate disease, and some evidence suggests that infectious triggers may serve as inciting events for AAV disease activity. Antibodies of the immunoglobulin (Ig)M isotype often serve as markers of recent infection, and IgM ANCA have been identified previously in patients with AAV, although the frequency and clinical relevance of IgM ANCA is not well established. We sought to characterize IgM ANCA more clearly by creating a novel enzyme‐linked immunosorbent assay (ELISA) for IgM antibodies to proteinase 3 [IgM proteinase 3 (PR3)–ANCA], which we applied to two large, clinically well‐characterized trial cohorts of patients with granulomatosis with polyangiitis and microscopic polyangiitis. In the first cohort, IgM PR3–ANCA occurred with a frequency of 15·0%, and were associated with a higher degree of disease severity and a trend towards a higher rate of alveolar haemorrhage (29·6 versus 15·7%, P = 0·10). Analysis of follow‐up samples in this cohort showed that the presence of IgM PR3–ANCA was transient, but could recur. In the second cohort, IgM PR3–ANCA occurred with a frequency of 41·1%, and were also associated with a higher degree of disease severity. A higher rate of alveolar haemorrhage was observed among those with IgM PR3–ANCA (45·3 versus 15·8%; P < 0·001). The association of transient IgM PR3–ANCA with an acute respiratory manifestation of AAV suggests a possible link between an infectious trigger and AAV disease activity. Abstract : Among participants of two large, clinically well‐characterized trial cohorts of patients with granulomatosis with polyangiitis and microscopic polyangiitis, IgM antibodies to proteinase 3 (IgM PR3‐ANCA) are transiently identified in a minority of subjects. The presence of IgM PR3‐ANCA is associated with a higher degree of disease activity and with a higher rate of alveolar hemorrhage. The authors speculate that the association of transient IgM PR3‐ANCA with a respiratory manifestation of ANCA‐associated vasculitis (AAV) could be due to a link between infectious triggers and AAV disease activity.